The Effect of β-glucan on Reducing HbA1c Levels in Patients with Diabetes Mellitus: A Meta Analysis Study - Huda, Putri Nabilla (Journal of Nutrition Science, 2025)
Diabetes mellitus is a non-communicable disease with a continuously increasing global prevalence and is characterized by elevated glycated hemoglobin (HbA1c), which reflects poor glycemic control and increases the risk of chronic complications. Nutritional management, particularly the intake of water-soluble dietary fiber such as β-glucan, has been proposed as an adjunct therapy for glycemic control. This study aimed to analyze the effect of β-glucan on reducing HbA1c levels in patients with diabetes mellitus through a meta analysis. Literature was retrieved from PubMed and ScienceDirect, and article selection followed the PRISMA flowchart, resulting in four eligible studies. Statistical analysis was performed by calculating the mean difference and 95% confidence interval using both common and random effects models, while heterogeneity was assessed using the I² statistic. The results showed that β-glucan intervention significantly reduced HbA1c levels, with greater reductions observed at doses ≥5 g/day and intervention durations ≥12 weeks. The common effect model demonstrated a mean difference of −0.57 (95% CI: −0.80 to −0.34; p < 0.0001), while the random effect model showed a mean difference of −0.50 (95% CI: −0.88 to −0.12; p = 0.0094). In conclusion, β-glucan effectively reduces HbA1c levels in patients with diabetes mellitus, with effectiveness influenced by dosage, duration, type of β-glucan, and participant characteristics, indicating its potential role in nutritional strategies for glycemic management.